The Importance of Forensic Psychiatry and Psychiatric Examination in Criminal Proceedings (Medico Legal Update, 2021)
Forensic examination, as part of the criminal process, is a complex activity in which the diagnostic momentis abnormally integrated, as the diagnosis is not intended for treatment or cure.It is understandable that the influence exerted by psychiatric examination on court decisions (it is mostlyabout psychiatry in general), cannot be separated from the historical relationship between psychiatry andlaw.In countries where the assessment of irresponsibility is based on a psychopathological-normative method,it is necessary not only to recognize the mental disorder, but also to assess how this disorder interactspsychologically in compromising the ability to understand actions and desire the advent of consequences.Reflecting on the above arguments, this paper focuses on the importance of forensic psychiatry andpsychiatric examination in criminal proceedings as a legal and medical study, as well as identifying criticalaspects of the inseparable relationship between psychiatry and law, until the moment when the judge willdecide whether the mental disorder under the Criminal Code prevented the perpetrator from understandingthe act committed, as well as whether or not he wished the consequences that came from this act.